Behavioral and Knowledge-Based Determinants of Tax Compliance: A Study on SMEs in North Medan, Indonesia - Adi Harianto; Fali, Ibrahim Mallam; Ahmad Rivai; Tyus Windi Ayuni; Rafida Khairani (YAYASAN BINA BISNIS NUSANTARA MEDAN, 2025)
This study examines the impact of accounting knowledge and taxpayer attitudes on tax compliance among Small and Medium Enterprises (SMEs) in North Medan. Using a quantitative approach, data were collected through surveys distributed to SME owners and managers who are directly involved in financial decision-making. The study found that both accounting knowledge and positive taxpayer attitudes significantly influence tax compliance. Accounting knowledge enables business owners to understand tax obligations and manage financial records accurately, leading to improved compliance. Meanwhile, taxpayer attitudes, such as the perception of fairness and trust in the tax system, also play a crucial role in determining the level of compliance. The results suggest that enhancing accounting education and fostering positive attitudes toward taxation could improve tax compliance in the SME sector. This research provides valuable insights for policymakers and tax authorities aiming to promote compliance through targeted educational programs and awareness campaigns.